Gas accumulation model of dolostones reservoirs beneath non-permeable layers controlled by faults: A case study of the middle-lower assemblage of Majiagou Formation in the Daniudi gas field - Tao LEI; Mingyuan TANG; Guanglei REN; Haoxiang LAN; Shuaijie YANG; Junyang ZHU; Mengdi CUI; Zhonghui CAI (地质科技通报, 2024)
Objective The dolomite of the Ordovician Majiagou Formation in the Ordos Basin, an important strategic replacement area, has been a research hotspot in recent years. There are few studies on the influence of faults on hydrocarbon accumulation in this set of dolomites. An unclear accumulation model has hindered further exploration and development of the middle and lower strata. Methods Using the middle and lower assemblages of the Majiagou Formation in the Daniudi Gas Field in the Ordos Basin as a case study, this paper comprehensively analyzes the reservoir distribution and trap types of presalt dolomite using data such as cores, thin sections, well logs, and fluid inclusions. The study analyzes the controlling effect of faults on gas-bearing properties. And the coupling relationship between multiphase fault activities and natural gas charging periods is clarified by establishing a fault-controlled mixed-source gas accumulation model with middle and lower combinations. Results The findings indicate show that (1) the natural gas accumulation in the middle assemblage of the Majiagou Formation has the advantage of dual-source hydrocarbon supply in the Upper and Lower Palaeozoic, forming a "sandwich" accumulation with two sets of source rocks flanking the middle reservoir. The gas source of the combination is mainly hydrocarbon supply from the source rocks in the lower Palaeozoic, and the accumulation combination of self-generation and self-storage is developed. (2) Karst reservoirs distributed along faults in the study area are the most important reservoir types in the middle and lower assemblages; trap types, including low-amplitude structural traps and diagenetic circle diagenetic traps, are mainly controlled by reservoir development mechanisms and are the main trap types in the study area. (3) The Majiagou Formation experienced three main periods of fault activity: the Caledonian, Indosinian, and Yanshanian-Hishanian periods. The faults and fissures that formed during the early Yanshan Movement were the most effective and were favourable for natural gas charging. (4) Diagenetic traps, multistage active faults and reservoir types controlled the natural gas accumulation process of the dolomite in the middle and lower Majiagou Formation, thus establishing a fault-controlled mixed-source gas accumulation model. Conclusion This study provides a theoretical framework for exploring subsalt dolomite gas reservoirs in fault-prone areas with similar geological conditions.